Comunicação empresarial e relações públicas: a construção de relacionamentos no contexto do Facebook - Maniero, Fabiana Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Currently with the context of the Internet, especially on online social networks, it is observed that people and companies are establishing relationships both online and offline. The new digital culture and the competitiveness of the market are making companies change the way they communicate with their customers, providing a broader and more participative communication with their stakeholders. This resear chaims to understand the relation of corporate communication and Public Relations and from the conceptualization of the trials will detect the relationship processes of companies and their public in online social networks. Understand this type of relation ship is interesting because that, it is the field of the Public Relations professional. An area that grows in importance in today's market, since Facebook is being used as a channel of communication and relationship with consumers. The methodology used is exploratory research, in which, it aims to familiarize themselves with the subject and the possibility of analyzing three examples of relationships and engagement in the corporate communications field. In this case, the ranking of the top three companies, Coca-Cola, Guaraná Antarctica e Mc Donald's, in the Top Facebook Posts Brazil in January 2015. It is important that to have a Public Relations Professional that is able to create an open channel of communication on social networks with the purpose of detecting the characteristics of the target public and promote the participation of such public in the building of content and the innovative organization process. Therefore, it becomes an engaging and everlasting relationship

No atual contexto da internet, mas especificadamente das redes sociais online, nota-se que as pessoas e as empresas estão se relacionando tanto no meio off-line quanto no online. A nova cultura digital e a competitividade de mercado fizeram com que as empresas alterassem o modo de se comunicar, proporcionando uma comunicação mais participativa e aberta com o público. Este estudo tem o intuito de conhecer a relação entre comunicação empresarial e relações públicas, e a partir da conceituação detectar como são realizados os processos de relacionamento das empresas como os seus públicos nas redes sociais online. Compreender este tipo de relação é interessante por ser uma área de atuação do profissional de relações públicas que cresce em importância no mercado, visto que o Facebook está sendo utilizado como canal de com unicação e relacionamento com o cliente. A metodologia adotada foi a pesquisa exploratória, a qual tem a finalidade de familiarização com o tema e também a possibilidade de analisar três exemplos de relacionamento e engajamento no campo da comunicação empresarial, no caso as três primeiras colocados, Coca-Cola, Guaraná Antarctica e Mc Donald's, no ranking do Top Facebook Posts Brasil no mês de janeiro de 2015. É importe que haja um profissional de relações públicas capaz de criar um canal aberto nas redes sociais com o intuito de detectar características do público-alvo e promover a participação do público na construção de conteúdos e processos da organização, para que desta forma seja de fato construídos relacionamentos engajados e duradouros
Keywords: Redes sociais on-line; Empresas; Facebook (Recursos eletrônicos); Redes sociais; Online social networks